Structural design and characterization of highly elastic woven fabric containing helical auxetic yarns. Issue 7 (April 2020) - Chen, Junli; Du, Zhaoqun; Li, Tianyuan
Auxetic textiles have been the focus of much attention due to their great promise for advanced protective clothing, flexible energy harvest devices, and functional textiles. Herein, plain fabric, basket fabric, and a derivative weave with the warp and weft yarns arrangement in a series of zigzags were prepared by incorporating different initial wrap density helical auxetic yarns in the weft direction using a commercial semi-automatic loom. The derivative weave using HAYs with a 150 m −1 initial wrap density as the weft yarn not only possesses superior auxetic behavior but also has good performance in strength and elasticity—essential properties useful for textile daily application. This fabric exhibits a high auxetic effect ( ν  = −0.585), low elastic deformation (total deformation of 8.4% at 20% strain), excellent flexibility, and high break load. Moreover, by taking account of the key geometric parameters, a systematic discussion of the fabrics has been completed to evaluate the effect on the auxetic behavior; this clarified that changing the fabric structure and initial wrap density of a HAY is an effective strategy to tailor auxetic behavior without compromising the intrinsic properties of components. On the basis of our research, auxetic textiles can be considered a promising candidate for next-generation smart textiles and advanced functional textiles.